Association between serum osteocalcin level and visceral obesity in Chinese postmenopausal women. (7th May 2015) - Luo, Yuqi; Ma, Xiaojing; Hao, Yaping; Xu, Yiting; Xiong, Qin; Tang, Junling; Pan, Xiaoping; Xiao, Yunfeng; Bao, Yuqian; Jia, Weiping
Summary Background A low serum osteocalcin level, visceral obesity and postmenopausal status are recognized risk factors for cardiovascular disease. Objective We investigated the relationship between the serum osteocalcin level and visceral fat content in a population of Chinese postmenopausal women. Design and patients In total, 1481 postmenopausal women (mean age ± standard deviation, 57·1 ± 4·8 years) were selected from the Shanghai Obesity Study. Measurements Abdominal fat accumulation was quantified using magnetic resonance imaging. Subjects with a visceral fat area (VFA) of ≥80 cm2 were classified as abdominally obese. The total serum osteocalcin level was measured by electrochemiluminescence immunoassay. Results The median serum osteocalcin level was 20·66 μg/l (interquartile range, 16·88–25·42 μg/l). The overall prevalence of abdominal obesity was 49·1% (n = 727). Abdominally obese subjects had lower serum osteocalcin levels than did nonabdominally obese subjects [19·14 (16·02–23·82) vs 21·97 (18·14–26·77) μg/l, respectively; P < 0·001]. Partial correlation analysis showed that the serum osteocalcin level was still negatively correlated with VFA after adjusting for age, years since menopause and body mass index (P < 0·01). Moreover, VFA was independently associated with the serum osteocalcin level after adjustment for confounding factors (P < 0·05). A low serum osteocalcin level was an independent risk factor for abdominal obesity (odds ratio, 0·972; 95% confidence interval, 0·953–0·991; P = 0·004). Conclusion The serum osteocalcin level was inversely correlated with the visceral fat content in these Chinese postmenopausal women.